Educação e linguagem na “Avaliação Diagnóstica Avaliar é TRI” do Rio Grande do Sul para o 3° ano do ensino médio de 2022 - Freitas, Janis Moreira de (My University, 2025)
This research is part of the research line "Educational Processes, Language, Technology, and Inclusion in Education" and aims to investigate how Oswald Ducrot's Theory of Polyphony can be applied as an analytical tool for the utterances found in the Avaliação Diagnóstica Avaliar é TRI assessment, with a focus on reading comprehension. The study is based on the premise that mother tongue education presupposes the development of reading comprehension skills, especially in formal assessment contexts.The theoretical framework is grounded in the contributions of Ferdinand de Saussure, Oswald Ducrot, Tânia Maris de Azevedo, as well as official educational documents that recognize reading as an essential skill to be developed in mother tongue teaching. The analysis focuses on the assessment administered to third-year high school students in a public school located in Caxias do Sul, RS, in 2022. Specifically, the research examines questions 4, 13, 16, and 25 from the assessment carried out by the State Government of Rio Grande do Sul, with the aim of analyzing how the utterances in these questions can be interpreted through the lens of the Theory of Polyphony.The goal is to analyze how Oswald Ducrot's Theory of Polyphony can be used as a tool to understand the utterances of the Avaliação Diagnóstica Avaliar é TRI assessment that presented the highest error rates, in order to investigate the relationship between these utterances and the reading comprehension skills of third-year high school students from a school in Caxias do Sul/RS in the year 2022. Ducrot's Theory of Polyphony is employed as an analytical tool to understand the multiple voices embedded in the assessment's utterances.The dissertation explores how meaning is constructed within these utterances and how this construction can influence students' reading comprehension, as well as how the utterances come together to form a network of meanings that must be interpreted by the test takers. In conclusion, the research contributes to the reflection on how diagnostic assessments can be more effective by taking into account the multiple layers of meaning that emerge from language, thus offering a more accurate evaluation of high school students' reading comprehension skills. It concludes that, although the Avaliação Diagnóstica Avaliar é TRI intends to assess reading comprehension, it ultimately fails to do so. [resumo fornecido pelo autor]
A pesquisa se insere na linha de pesquisa "Processos Educacionais, Linguagem, Tecnologia e Inclusão na Educação" e tem como objetivo investigar como a Teoria da Polifonia de Oswald Ducrot pode ser aplicada como instrumento de análise dos enunciados da Avaliação Diagnóstica Avaliar é Tri, com foco na compreensão leitora. O estudo parte da premissa de que o ensino de língua materna pressupõe o desenvolvimento da habilidade de compreensão de textos, especialmente em contextos formais de avaliação. A dissertação utiliza como referencial teórico as contribuições de Ferdinand de Saussure, Oswald Ducrot, Tânia Maris de Azevedo e documentos normativos no âmbito educacional, que reconhecem a leitura como uma habilidade essencial a ser desenvolvida no ensino de língua materna. A análise concentrou-se na avaliação aplicada aos estudantes do 3o ano do Ensino Médio de uma escola localizada em Caxias do Sul/RS, em 2022. Especificamente, a pesquisa foca nas questões 4, 13, 16 e 25 da avaliação realizada pelo Governo Estadual do Rio Grande do Sul, com o intuito de analisar como os enunciados dessas questões podem ser compreendidos à luz da Teoria da Polifonia. O objetivo foi analisar de que maneira a Teoria da Polifonia de Oswald Ducrot pode ser aplicada como ferramenta para compreender os enunciados da prova Avaliação Diagnóstica Avaliar é TRI que apresentam maior índice de erro, com o intuito de investigar a relação desses enunciados com a habilidade de compreensão leitora dos estudantes do 3o ano do Ensino Médio de uma escola de Caxias do Sul/RS, no ano de 2022s. A Teoria da Polifonia de Ducrot foi utilizada como uma ferramenta analítica para compreender as várias vozes presentes nos enunciados da avaliação. A dissertação investiga como a construção de sentidos nos enunciados pode afetar a compreensão leitora dos estudantes e como esses enunciados se articulam para formar um campo de significados que precisa ser compreendidos pelos avaliados. Ao final, a pesquisa contribui para a reflexão sobre como as avaliações diagnósticas podem ser mais eficazes ao considerar as múltiplas possibilidades de sentido que emergem da linguagem, oferecendo uma avaliação mais precisa das habilidades de leitura dos estudantes do Ensino Médio e conclui que Avaliação diagnóstica Avaliar é TRI propõe-se avaliar a compreensão leitora, no entanto não o faz. [resumo fornecido pelo autor]
Keywords: Análise do discurso; Linguística; Linguagem e línguas; Ducrot, Oswald, 1930-2024; Avaliação educacional; Educação - Rio Grande do Sul; Discourse analysis; Linguistics; Language and languages; Educational evaluation; Education - Rio Grande do Sul (Brazil)